2017
DOI: 10.4194/1303-2712-v17_1_03
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The main goal of this study is to determine the composition, diversity and ecology of benthic diatoms in Karagöl Lake in Karagöl-Sahara National Park. Monthly sampling (from sediments, stones and aquatic plants in littoral zone of the lake) taken in three consecutive years revealed 57 diatom taxa with Gomphonema and Pinnularia being the most abundant species while other genera are represented with three or fewer species. Lindavia ocellata was the most dominant taxon in the samplings examined throughout the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The identified diversity, including 71 taxa of species rank and below, turned out to be similar in species richness to other high mountain lakes, such as Artabel, as well as some others in northern Turkey [42,49]. The head part of studied diatom flora of both lakes represented only four genera species: Eunotia (8), Gomphonema (6), Pinnularia (6), and Navicula (5) that is similar to the other high mountain lakes in Turkey and Europe [4,42,[53][54][55][56][57][58][59]. With the dominance of Eunotia species, as well as the noticeable presence of Pinnularia, which both prefer low conductivity and slightly acidic freshwater [60], the results of this study characterize the lake water as mostly circumneutral and acidic and have low mineral content [38].…”
Section: Discussionmentioning
confidence: 90%
“…The identified diversity, including 71 taxa of species rank and below, turned out to be similar in species richness to other high mountain lakes, such as Artabel, as well as some others in northern Turkey [42,49]. The head part of studied diatom flora of both lakes represented only four genera species: Eunotia (8), Gomphonema (6), Pinnularia (6), and Navicula (5) that is similar to the other high mountain lakes in Turkey and Europe [4,42,[53][54][55][56][57][58][59]. With the dominance of Eunotia species, as well as the noticeable presence of Pinnularia, which both prefer low conductivity and slightly acidic freshwater [60], the results of this study characterize the lake water as mostly circumneutral and acidic and have low mineral content [38].…”
Section: Discussionmentioning
confidence: 90%
“…It was reported that 1,4-diazines and 1,4-thiazines were synthesized via the condensation of 1,2-diamines with 1,2-dicarbonyl compounds or 2-aminothiophenol with maleic anhydride. [31,32] In our study, cyclization was performed by the condensation of the dicarbonyl derivative 2b with phenylene diamine and 2-aminothiophenol producing compounds 3 and 4, whose structures were proven by disappearance of the carbonyl group bands at 1,700 and 1,680 cm −1 and detection of C=N band at 1,541 cm −1 . The 1 HNMR | 573 mMOHmMED MetHal spectrum of 3 showed triplet signal at δ 7.38 ppm of both benzothiazole-C 5,6 -H and quinoxaline-C 6,7 -H, while doublet signal at δ 7.94 ppm with J = 7.50 Hz was assigned to benzothiazole-C 4,7 -H and quinoxaline-C 5,8 -H, and that of 4 showed the appearance of singlet signal at δ 2.82 ppm due to the thiazole-C 4 -H, triplet signal at δ 7.43 ppm of both benzothiazole-C 5,6 -H and benzothiazine-C 6,7 -H, while doublet signal at δ 7.93 ppm with J = 7.50 Hz was assigned to both benzothiazole-C 4,7 -H and benzothiazine-C 5,8 -H.…”
Section: Chemistrymentioning
confidence: 98%